Write an equation for (2x +3) and (x-6)
7 answers
(2x + 3)(x - 6)
What does it equal to?
Expanding the expression (2x + 3)(x - 6):
= 2x(x - 6) + 3(x - 6)
= 2x^2 - 12x + 3x - 18
= 2x^2 - 9x - 18
Therefore, the equation (2x + 3)(x - 6) is equal to 2x^2 - 9x - 18.
= 2x(x - 6) + 3(x - 6)
= 2x^2 - 12x + 3x - 18
= 2x^2 - 9x - 18
Therefore, the equation (2x + 3)(x - 6) is equal to 2x^2 - 9x - 18.
(2 x+3)+ (x-6)
Simplifying the expression (2x + 3) + (x - 6):
= 2x + 3 + x - 6
= 3x - 3
Therefore, (2x + 3) + (x - 6) simplifies to 3x - 3.
= 2x + 3 + x - 6
= 3x - 3
Therefore, (2x + 3) + (x - 6) simplifies to 3x - 3.
(2 x+3)+ (x-6)=
The given expression is (2x + 3) + (x - 6).
It can be simplified by combining like terms:
(2x + 3) + (x - 6)
= 2x + x + 3 - 6
= 3x - 3
Therefore, (2x + 3) + (x - 6) simplifies to 3x - 3.
It can be simplified by combining like terms:
(2x + 3) + (x - 6)
= 2x + x + 3 - 6
= 3x - 3
Therefore, (2x + 3) + (x - 6) simplifies to 3x - 3.